Simulation numerique du soufflage et du thermoformage des plastiques - Rachi, Mohamed; Roelandt, Jean-Marie; Batoz, Jean-Louis (European Journal of Computational Mechanics, 1994)
The explicit dynamic algorithm commonly used to solve sheet metal forming problems, has been applied to solve two plastic transformation processes : blow molding and thermoforming. Constitutive laws which properly represent polymer at processing temperature have been considered. We have compared the thickness and stress distributions for hyperelastic and viscoelastic models. Two examples on blow molding and thermoforming lwve been studied and the numerical results have been compared with experimental data.